2014
DOI: 10.1016/j.jaci.2014.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Atopic phenotypes identified with latent class analyses at age 2 years

Abstract: Background Atopic sensitization or atopy is the most commonly reported risk factor for asthma. Recent studies have begun to suggest that atopy, as conventionally defined, may be an umbrella term that obfuscates more specific allergic disease types. Objective To determine if distinct and meaningful atopic phenotypes exist within a racially diverse birth cohort using ten allergen-specific IgE (sIgE) measurements from children of age 2 years. Methods Using the WHEALS birth cohort (62% Black), we analyzed sIgE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 28 publications
1
73
0
1
Order By: Relevance
“…[19][20][21][22] In 2016, LCA method was also used to identify phenotypes of atopic sensitization. 23,24 To our knowledge, this is one of the first studies using the LCA method to evaluate different subtypes of atopic dermatitis in childhood. The strengths of this study are the large population design of the PASTURE study and the repeated data on atopic dermatitis symptoms, prospectively collected from birth to school age, which give the opportunity to use this method.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] In 2016, LCA method was also used to identify phenotypes of atopic sensitization. 23,24 To our knowledge, this is one of the first studies using the LCA method to evaluate different subtypes of atopic dermatitis in childhood. The strengths of this study are the large population design of the PASTURE study and the repeated data on atopic dermatitis symptoms, prospectively collected from birth to school age, which give the opportunity to use this method.…”
Section: Discussionmentioning
confidence: 99%
“…Although atopic children do not always develop asthma, recent data have indicated that allergic children who exhibit multiple early-life (age 2) sensitizations to a range of allergens, for example, dog, cat, cockroach, egg, peanut, are at a significantly higher risk for subsequently developing physician diagnosed asthma at age 4 (odds ratio, 5.3; 95% confidence interval, 1.6-17.4), compared with those who are either nonsensitized or sensitized to only one or two of these allergens [20]. Indeed, murine studies examining neonatal mice whose airways were sensitized with house dust mite (HDM) demonstrated more pronounced allergic airway inflammation compared with similarly challenged adult animals [21 & ].…”
Section: Early-life Airway Microbiome and Allergic Asthmamentioning
confidence: 99%
“…This balance ranges between the extremes of Treg cell dominance (absolute tolerance/no evidence of IgE production) and strong T H 2 memory dominance (ie, multiple sensitizations/high IgE/high asthma risk). 18,19 However, a very common outcome is an apparently ''mixed'' memory response in which sufficiently high levels of T H 2 memory persist to drive ongoing IgE production but not to mediate the repeated cycles of aeroallergen-induced acute-phase (IgE-FcR-mediated) plus late-phase (T H 2 effector-mediated) responses responsible collectively for the severe airways inflammation necessary to drive asthma pathogenesis. The existence of such balanced but seemingly ''benign'' T H 2 memory responses is evident from data from some of the large birth cohort studies exemplified in Fig 1. These data come from the 14-year respiratory follow-up of our RAINE cohort, 20 in which approximately 40% of the 1380 subjects assessed were sensitized to the perennial indoor allergen house dust mite but only a minority of these exhibit wheezing symptoms.…”
Section: Myeloid Dendritic Cell (Mdc)mentioning
confidence: 99%